SKENARIO KEBIJAKAN PENGELOLAAN HUTAN RAKYAT BERKELANJUTAN DI KABUPATEN BOGOR - Tatan Sukwika; Dudung Darusman; Cecep Kusmana; Dodik Ridho Nurrochmat (Graduate School Bogor Agricultural University (SPs IPB), 2018)
This study discusses the policy scenarios on private-forest management in Bogor. The aims of this study are: determining leverage attribut on private-forest and formulating policy models, and making scenario for the development of the sustainability index of privately managed forest. This study uses multidimensional scalling (MDS) to analyze five dimensions. By using ordinal score on certain attribute, i.e. 0 (the lowest) and 10 (the highest) of each attribute. Then, by using Rap-Pforest, we could estimate the leverage attribute of f each dimension. To prepare policy models will use a prospective analysis. Final stages, to build strategic scenarios model. The analysis showed that there are two dimensions, i.e. ecology and legal and institutional, are moderately sustainable. While for the dimensions of economy, socio-culture, and accessibility and technology are less sustain. Based on five dimensions sustainability index, this study concludes that63 indicators were used and resulting 21 leverage-attributes. Qualitative model formulation for policy scenarios are: HRB = f (EKN3, EKN4, SOS1, SOS3, LBG2, LBG3). Scenario II most realistic choice, this scenario has been able to increase the value of sustainability index of 46.35 (less sustainable) to 52.52 (quite sustainable). This study recommends, it is necessary to conduct the development strategy by involving all stakeholders as the most appropriate policy options to improve the sustainability of small scale privately managed forest in Bogor.